The coagulant dipping process of nitrile latex: investigations of former motion effects and coagulant loss into the dipping compound. Issue 3 (19th December 2022) - Groves, Robert; Welche, Patrick; Routh, Alexander F.
Abstract : Coagulant dipping, the process used in thin glove manufacture, involves electrolyte ions diffusing from the surface of a hand-shaped former into latex compound, causing a deposit (wet gel) to accumulate on the former. Abstract : Coagulant dipping, the process used in thin glove manufacture, involves electrolyte ions diffusing from the surface of a hand-shaped former into latex compound, causing a deposit (wet gel) to accumulate on the former. In this work, two aspects of the process were examined, both experimentally and theoretically. For the experimental work, a commercial nitrile latex was used. The motion of formers through a latex dipping tank is intuitively expected to affect the electrolyte diffusion and hence the wet gel growth. This was investigated at laboratory scale with small glass formers moving in a metre-long dip tank. Former velocities ranged from zero to almost 0.2 m s −1 . No effect of former lateral movement on wet gel thickness was observed. One obvious explanation is that most of the coagulant diffusion occurs within the wet gel deposit, which provides protection to the diffusive flux. However, the critical zone is just ahead of the coagulating front, where coagulant is present in the liquid compound at concentrations below the level needed for coagulation. A fluid mechanical model was constructed that assumed a uniform fluid flow along the side face of a rectangular former. The model confirmed that for calcium nitrate, the most commonly used coagulant, the effect of movement is very small. In the second investigation, coagulant leakage into the host latex compound during the dwell time was investigated by taking samples during repeat static dips. This experiment was modelled using diffusion theory, focusing on the critical zone just outside the wet gel at the point of former withdrawal. The model and experiment agreed well, both showing a small but definite coagulant leakage that tended towards a plateau concentration. Coagulant leakage from a moving former was also considered, from a theoretical perspective. In this case, the mechanism is advective movement of coagulant from the critical zone into the host compound. In the worst case, where all of this coagulant is swept away, the model suggested that the plateau coagulant concentration could reach an amount that would cause coagulation. Reduced flow in the critical zone (boundary layer) and former shape are factors that would reduce leakage.